PKM mendesain media pembelajaran berbasis e-learning pada guru-guru di Sekolah Dasar Malino - Purnamawati Purnamawati; Hasanah Hasanah (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Designing learning media based on e-learning in Malino Elementary School is an important program of activities to beimplemented in the digital era in order to improve the teaching competencies of productive teachers through 21st centurylearning. e-learning. Based on the problems of partners, realized by PKM designing e-learning based learning media with the aimto: (1) increase knowledge in the preparation of e-learning based learning media, and (2) increase understanding of thecomponents of e-learning based learning media development. Methods of activities through guidance and training (practice),methods of discussion and evaluation. Outputs and results achieved after doing this activity, namely: Outputs and results thathave been achieved, namely (1) the teachers have knowledge of the steps in the preparation of e-learning based learning media,(2) the teachers compile an e-based learning media -learning with approaches according to core competencies and basiccompetencies, (3) the absorption of mastery of the average training material is good, (4) the teachers give positive responses tothe implementation of the training, and (5) the teachers are able to make and use e-learning based learning media. Based on theresults achieved, the implementation of PKM design of e-learning based learning media for teachers was successful. Therefore,teachers get contextual guidance during training. Starting from the design of teaching materials, knowing the features that areused in stages in e-learning based learning and implementing it well.